Equity Impacts of Transportation Improvements On Core and Peripheral Cities - Eran Leck; Shlomo Bekhor; Daniel Gat (Journal of Transport and Land Use)
The aim of this paper is to assess the short-term impact of transportation improvements on the reduction of socio-economic disparities between core and peripheral cities. Data used in the analysis was extracted from the 1995 Israel Census. The methodology applied in the study was to estimate discrete choice models in an attempt to identify key variables affecting commuting decisions. Policy simulations are employed to illustrate the effect of diminishing spatial friction on wage convergence between poor southern towns and affluent core cities. The empirical evidence suggests that transportation improvements, especially in the form of introducing new rail links in underserved cities, could significantly contribute to the alleviation of spatial wage disparities between core and peripheral cities.